Intra-group stigma: Examining peer relationships among women in recovery for addictions. (June 2015) - Gunn, Alana J.; Canada, Kelli E.
Abstract This grounded theory study explores how women with histories of addiction perceive stigma while in treatment. In-depth interviews were conducted with 30 women participating in a residential drug treatment centre. Previous research has found that support from peers during recovery can be critical to managing illnesses. In fact, researchers have postulated that peers can be a more effective form of support than even family. This study extends existing literature indicating that peer support systems can be supportive, however they can also can be perceived as negative support that impose stigmas. Findings reveal that women perceive stigmas due to how various types of drug use violate societal expectations and conflict with notions of deservingness. Specifically, the "hard users" (i.e. women who use heroin or crack cocaine) perceive stigmas regarding how their drug use violates norms of womanhood. Moreover, the "soft users" (i.e. those who use alcohol or marijuana) perceive stigmas that their drug use is considered undeserving of support. This article explores the factors that contribute to stigma amongst populations who potentially face marginalisation from larger society. Implications for treatment and group work are discussed.